Proceedings of the 2021 International Conference on Financial Management and Economic Transition (FMET 2021) 2021
DOI: 10.2991/aebmr.k.210917.070
|View full text |Cite
|
Sign up to set email alerts
|

The Comprehensive Competitiveness of Tesla Based on Financial Analysis: A Case Study

Abstract: Contemporarily, the new energy automobile industry has developed rapidly, which has attracted plenty of investors due to the great market potential. The increasing listed companies lead to fierce competition in this industry, i.e., it is crucial to analyse the comprehensive competitiveness of these companies for both industry and investors. Based on relative literatures, Tesla, a leader in the industry, is selected as a case to analyse. Specifically, we used Tesla's financial statements from 2018 to 2020 and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Qin et al chose EV industry leader Tesla as a case and compared its financial statements from 2018 to 2020 with other competitors in the EV industry to analyze its comprehensive competitiveness. Through the case study method, the author points out the existing problems of Tesla and puts forward some feasible suggestions, which will help investors make the right investment decision [6]. In order to inform the desire for growth in the EV market held by investors, the authors study and quantify the main determinants of future EV demand.…”
Section: Related Researchmentioning
confidence: 99%
“…Qin et al chose EV industry leader Tesla as a case and compared its financial statements from 2018 to 2020 with other competitors in the EV industry to analyze its comprehensive competitiveness. Through the case study method, the author points out the existing problems of Tesla and puts forward some feasible suggestions, which will help investors make the right investment decision [6]. In order to inform the desire for growth in the EV market held by investors, the authors study and quantify the main determinants of future EV demand.…”
Section: Related Researchmentioning
confidence: 99%
“…While Tesla has shortened its global operations, it has also implemented layoffs and pay cuts for temporary employees, leading to the forced departures of some employees. Tesla mentioned in its financial statement that in April 2020, due to the outbreak of covid-19, many temporary employees were laid off, and the base salary of other employees was reduced [6]. The wage cut sparked employee dissatisfaction, leading to employees resigning from Tesla [6].…”
Section: Covid-19 Impact and Logistic Problemmentioning
confidence: 99%
“…Tesla mentioned in its financial statement that in April 2020, due to the outbreak of covid-19, many temporary employees were laid off, and the base salary of other employees was reduced [6]. The wage cut sparked employee dissatisfaction, leading to employees resigning from Tesla [6]. In the future, when Tesla wants to expand its scale to recruit some new employees, there will be a labor shortage problem.…”
Section: Covid-19 Impact and Logistic Problemmentioning
confidence: 99%
“…The fundamental analysis of the financial statements of Tesla ltd by the author concluded that it is a good choice to invest in the firm. Qin et al (2021) did a case on Tesla Inc. where the financial performance of the company was compared with its competitors in the same industry based on various financial ratios, capital structure leverage and return on capital employed (ROCE) was studied. The main objective of the study was to find out the level of competitiveness in the electric vehicle automotive industry.…”
Section: Introductionmentioning
confidence: 99%